Effects of exposure to high temperatures on serum, urine and sweat concentrations of iron and copper. (April 2020) - Siquier-Coll, J.; Bartolomé, I.; Perez-Quintero, M.; Grijota, F.J.; Muñoz, D.; Maynar-Mariño, M.
Abstract: The objective of this research was to determine the acute effect of a maximum test until exhaustion in normothermia and hyperthermia, and after repeated exposure to heat at high temperatures on the homeostasis of Fe and Cu. The sample was composed of twenty-nine male university students. The participants were divided into a control group (CG) and an experimental group (EG). All of them underwent an incremental test until exhaustion in normothermia and hyperthermia before and after the repeated exposure of EG to heat at high temperatures, consisting of 9 heat acclimatisation sessions in the sauna. Samples of urine and blood were taken before and after each test. Additionally, sweat samples were collected in the hyperthermia test. The samples were frozen at −80 °C for further analysis by ICP-MS. None of the metal concentrations in serum were affected by hyperthermia or exposure to heat. Urinary Fe increased in CG in the hyperthermia test before Heat exposure at High Temperature (HEHT)(p < 0.05) and in both groups after HEHT (p < 0.05). In EG there was an increase in the urinary excretion of Cu after HEHT (p < 0.01) in both trials. Fe suffered a decrease in sweat in EG after exposure to heat (p < 0.05). The concentrations of Fe and Cu in serum were not affected by acute exercise and exposure to high temperatures. However, there was a decrease in excretion of Fe in sweat due to HEHT, and an increase in urinary excretion in both. Therefore, we think that in conditions of high temperatures for long periods of time, attention should be paid to the body levels of these metals. Highlights: This line of research on iron, copper and heat exposure is innovative. The effects after intense heat exposure in three weeks on these metals are not clear. After nine heat exposures, the urinary excretion of these metals grew after exercise. The supplementation of these elements could be necessary in hot environments.